Formation of the Stomatal Outer Cuticular Ledge Requires a Guard Cell Wall Proline-Rich Protein . Issue 2 (2nd February 2017) - Hunt, Lee; Amsbury, Samuel; Baillie, Alice; Movahedi, Mahsa; Mitchell, Alice; Afsharinafar, Mana; Swarup, Kamal; Denyer, Thomas; Hobbs, Jamie K.; Swarup, Ranjan; Fleming, Andrew J.; Gray, Julie E.
Abstract : Plants lacking the guard cell-expressed, proline-rich secreted protein FOCL1 are drought tolerant because they fail to form a stomatal cuticular ledge and produce stomatal pores that are covered by a continuous cuticle. Abstract: Stomata are formed by a pair of guard cells which have thickened, elastic cell walls to withstand the large increases in turgor pressure that have to be generated to open the pore that they surround. We have characterized FOCL1, a guard cell-expressed, secreted protein with homology to Hyp-rich cell wall proteins. FOCL1-GFP localizes to the guard cell outer cuticular ledge and plants lacking FOCL1 produce stomata without a cuticular ledge. Instead the majority of stomatal pores are entirely covered over by a continuous fusion of the cuticle, and consequently plants have decreased levels of transpiration and display drought tolerance. The focl1 guard cells are larger and less able to reduce the aperture of their stomatal pore in response to closure signals suggesting that the flexibility of guard cell walls is impaired. FOCL1 is also expressed in lateral root initials where it aids lateral root emergence. We propose that FOCL1 acts in these highly specialized cells of the stomata and root to impart cell wall strength at high turgor and/or to facilitate interactions between the cell wall and the cuticle.